Pengaruh Literasi Digital dan Keberlanjutan Bisnis terhadap Ekonomi Kreatif dengan Sikap Kewirausahaan sebagai Variabel Intervening - Basori, Mohamat; Intan, Lusi Reni; Triana, Ade; Wahyono, Budi; Dila, Fara; Hidayat, Arif (CV ODIS, 2025)
The digital transformation era has brought new opportunities for the creative economy sector, yet not all entrepreneurs have fully embraced its potential. This study aims to explore how digital literacy and business sustainability influence the growth of the creative economy, with entrepreneurial attitude serving as a mediating variable. A quantitative approach with SEM-PLS analysis was applied, using data from 256 MSME actors in the creative economy across Jabodetabek. The findings reveal that entrepreneurial attitude plays the most dominant role in fostering creative economic development. Business sustainability also has a significant impact, both directly and indirectly, through entrepreneurial attitude. In contrast, digital literacy exerts a relatively smaller effect but becomes meaningful when mediated by entrepreneurial behavior. The study highlights the importance of cultivating entrepreneurial character alongside digital and sustainability training. Given the study’s geographic and sample limitations, future research is recommended to expand to broader regions and explore additional variables such as innovation and government policy support.